Effect of Attention Based Exercises in Balance Control and Fall Risk in Elderly Females - An Interventional Study - Arunima Sasidharan; L Gladson Jose (RGUHS Journal of Physiotherapy)
Background Aim Fall related injuries in elderly population are one of the most disabling predicaments particularly in the age group of 60-70 years. Postural restoration therefore is one of the major concerns demanding attention in elderly individuals with balance impairments. This study aimed to determine the effect of attention focussed balance interventions in improving balance and reducing the risk of falling in female elderly population.Methods In this experimental interventional study 54 subjects in the age range of 60-70 years with age related balance impairments were recruited from an old age home using purposive sampling technique with the set inclusion and exclusion criteria. Group A n27 Experimental group received attention-based balance exercise intervention for five daysweek for a total duration of 12 weeks and Group B n27 Control group received normal mobility training for five days week for 12 weeks. Outcome measures included Berg balance scale and John Hopkins Fall Risk Assessment Tool.Results Results after statistical analysis within and between groups indicated that Group A subjects highly benefitted from the attention focussed intervention provided to them for 12 weeks duration 36.37-47.26. In Group B though a significant difference was noted in the balance of individuals changes were less compared to the experimental group with a t value of -16.480 and a P value of 0.000.Conclusion Application of a component of cognition i.e. attention along with balance exercises can rectify the balance impairments and reduce the risk of falls in this population.